Response and Approach of Muhammadiyah in Addressing the Phenomenon of Digital Cryptocurrency in Urban Communities - Aris Munandar, Siswoyo; Fahrurrozi, M. (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
The phenomenon of cryptocurrency adoption among Indonesia's urban communities is on the rise, following rapid digital economic development. However, the involvement of Muslim communities—including Muhammadiyah members—has sparked ethical and Islamic legal debates regarding the legitimacy and safety of cryptocurrencies. Diverse perspectives among religious authorities and the low level of digital sharia literacy underscore the importance of Muhammadiyah’s response and approach to this issue. This study aims to elaborate on Muhammadiyah’s response, legal (fatwa) arguments, and approaches regarding the phenomenon of cryptocurrencies, particularly in urban environments that are vulnerable to speculative investment and lack sharia understanding. The research uses a qualitative descriptive method with literature review, analyzing official fatwas, academic literature, and Muhammadiyah’s religious education practices related to cryptocurrency. It also includes a comparative analysis with other Islamic authorities in Indonesia. The Tarjih and Tajdid Council of Muhammadiyah has issued a fatwa declaring the use of cryptocurrency, as both a means of exchange and an investment instrument, as haram. The main reasons for this decision are its speculative nature (maysir), uncertainty (gharar), extreme volatility, and lack of clear underlying asset. Muhammadiyah believes cryptocurrency does not satisfy sharia economic principles and tends to bring harm to society. Muhammadiyah’s approach emphasizes community-based education, digital da’wah, and the enhancement of sharia financial literacy to protect urban communities from speculative investments and digital fraud risks.